Modulation of Myostatin/Hepatocyte Growth Factor Balance by Different Hemodialysis Modalities. (28th March 2017) - Esposito, Pasquale; La Porta, Edoardo; Calatroni, Marta; Grignano, Maria Antonietta; Milanesi, Samantha; Verzola, Daniela; Battaglia, Yuri; Gregorini, Marilena; Libetta, Carmelo; Garibotto, Giacomo; Rampino, Teresa
Abstract : Background. In this study we investigated the relevance of myostatin and Hepatocyte Growth Factor (HGF) in patients undergoing hemodialysis HD and the influence of different HD modalities on their levels. Methods. We performed a prospective crossover study in which HD patients were randomized to undergo 3-month treatment periods with bicarbonate hemodialysis (BHD) followed by online hemodiafiltration (HDF). Clinical data, laboratory parameters, and myostatin and HGF serum levels were collected and compared. Results. Ten patients and six controls (C) were evaluated. In any experimental condition myostatin and HGF levels were higher in HD than in C. At enrollment and after BHD there were not significant correlations, whereas at the end of the HDF treatment period myostatin and HGF were inversely correlated (r - 0.65, p < 0.05 ), myostatin serum levels inversely correlated with transferrin (r - 0.73, p < 0.05 ), and HGF levels that resulted positively correlated with BMI (r 0.67, p < 0.05 ). Moving from BHD to HDF, clinical and laboratory parameters were unchanged, as well as serum HGF, whereas myostatin levels significantly decreased (6.3 ± 4.1 versus 4.3 ± 3.1 ng/ml, p < 0.05 ). Conclusions. Modulation of myostatin levels and myostatin/HGF balance by the use of different HD modalities might represent a novel approach to the prevention and treatment of HD-related muscle wasting syndrome.